2002
DOI: 10.1088/0031-9155/47/18/308
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative fluorescence lifetime spectroscopy in turbid media: comparison of theoretical, experimental and computational methods

Abstract: A Monte Carlo model developed to simulate time-resolved fluorescence propagation in a semi-infinite turbid medium was validated against previously reported theoretical and computational results. Model simulations were compared to experimental measurements of fluorescence spectra and lifetimes on tissue-simulating phantoms for single and dual fibre-optic probe geometries. Experiments and simulations using a single probe revealed that scattering-induced artefacts appeared in fluorescence emission spectra, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 55 publications
1
82
1
2
Order By: Relevance
“…To date, NIR techniques have been combined with several high spatial resolution, structure-specific imaging modalities including X-ray tomosynthesis 57 , ultrasound 66,74 , and MRI [75][76][77] , to study human tissues and small animals. Past experiences have contributed to a variety of imaging systems, imaging geometries, and numerical reconstruction techniques, but…”
Section: Multimodality Techniquesmentioning
confidence: 99%
“…To date, NIR techniques have been combined with several high spatial resolution, structure-specific imaging modalities including X-ray tomosynthesis 57 , ultrasound 66,74 , and MRI [75][76][77] , to study human tissues and small animals. Past experiences have contributed to a variety of imaging systems, imaging geometries, and numerical reconstruction techniques, but…”
Section: Multimodality Techniquesmentioning
confidence: 99%
“…However, it requires a statistically meaningful number of photons and hence can be time consuming. The Monte Carlo technique has been used by Vishwanath et al [11] to simulate time-resolved fluorescence from semi-infinite homogeneous turbid media. It was shown that the recovered lifetimes increased with increasing scattering and source-detector distance.…”
Section: Current State Of Knowledgementioning
confidence: 99%
“…The Monte Carlo code had been validated for fluorescence lifetime spectroscopy 32 . We performed calculations using a slab with a thin top layer (5 (mm)) and a much larger (semi-infinite) bottom layer.…”
Section: Nirfastmentioning
confidence: 99%